Pelatihan Blended Learning pada Guru SMA Katolik 1 Kabanjahe - Sanjaya Pinem; Viktor Edison Hutagaol (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2021)
Abstract: Technology information using the internet can benefit educators and provide information to students to transfer knowledge has a very high potential. The purposes of these community service are: (1) to expand the insight, knowledge, and experience directly about the model of blended learning for teachers, especially teachers of Sma Katolik 1 Kabanjahe; (2) Teachers can use elearning moodle learning technology. The techniques that are planned to shape the motivation and participation of educators ranging from the benefits of blended learning, and the application of blended learning so that educators in directly implementing it in the classroom. The implementation method starts in a structured manner starting from the initial discussion about blended learning, taking the results of the initial questionnaire, then giving independent tasks to the teachers. This community service was attended by 12 teachers at SMA Katolik 1 Kabanjahe, Kab. Karo. North Sumatra. The important conclusion of this community service is the awareness and ability of educators in using information technology, especially blended learning can increase motivation to educators to provide maximum learning to learners.         Keywords: blended learning; moodle; teaching technologyAbstrak: Teknologi informasi dengan menggunakan internet dapat menguntungkan para pendidik dalam memberikan informasi kepada peserta didik. Pengetahuan tentang teknologi informasi mempunyai potensi yang sangat tinggi. Tujuan dari penulisan: (1) memperluas wawasan, pengetahuan dan pengalaman secara langsung tentang model pembelajaran blended learning untuk guru guru khususnya Guru SMA Katolik 1 Kabanjahe; (2) Guru–guru dapat menggunakan teknologi pembelajaran elearning moodle. Teknik yang direncanakan untuk membentuk motivasi dan partisipasi tenaga pendidik mulai dari keuntungan blended learning, dan pengaplikasian blended learning sehingga tenaga pendidik dalam langsung mengimplementasikannya di dalam kelas. Metode pelaksanaan dimulai secara terstruktur mulai dari diskusi awal tentang blended learning, mengambil hasil kuesioner awal, selanjutnya memberikan tugas mandiri kepada guru–guru. Pelaksanaan pengabdian kepada masyarakat ini diikuti oleh 12 guru di SMA Katolik 1 Kabanjahe, kab. Karo. Sumatera Utara. Kesimpulan penting dari pengabdian ini adalah adanya kesadaran dan kemampuan pendidik dalam menggunakan teknologi informasi khususnya blended learning dapat meningkatkan motivasi kepada tenaga pendidik untuk memberikan pembelajaran yang maksimal kepada peserta didik.Kata kunci: blended learning; moodle; teknologi pembelajaran